Zero ischemia robotic-assisted partial nephrectomy in Alberta: Initial results of a novel approach - Forbes, Ellen; Cheung, Douglas; Kinnaird, Adam; St. Martin, Blair (Canadian Urological Association Journal, 2015)
Introduction: Partial nephrectomy remains the standard of care in early stage, organ-confined renal tumours. Recent evidence suggests that minimally invasive surgery can proceed without segmental vessel clamping. In this study, we review our experience at a Canadian centre with zero ischemia robotic-assisted partial nephrectomy (RAPN). Methods: A retrospective chart review of zero ischemia RAPN was performed. All surgeries were consecutive partial nephrectomies performed by the same surgeon at a tertiary care centre in Northern Alberta. The mean follow-up period was 28 months. These outcomes were compared against the current standards for zero ischemia (as outlined by the University of Southern California Institute of Urology [USC]). Results: We included 21 patients who underwent zero ischemia RAPN between January 2012 and June 2013. Baseline data were similar to contemporary studies. Twelve (57.1%) required no vascular clamping, 7 (33.3%) required clamping of a single segmental artery, and 2 (9.5%) required clamping of two segmental arteries. We achieved an average estimated blood loss of 158 cc, with a 9.2% average increase in creatinine postoperatively. Operating time and duration of hospital stay were short at 153 minutes and 2.2 days, respectively. Conclusion: Zero ischemia partial nephrectomy was a viable option at our institution with favourable results in terms of intra-operative blood loss and postoperative creatinine change compared to results from contemporary standard zero ischemia studies (USC). To our knowledge, this is the first study to review an initial experience with the zero ischemia protocol in robotic-assisted partial nephrectomies at a Canadian hospital.